Immunomorphological aspects of oropharynx squamous cell carcinoma prognosis. - Poslavskaya, A. V. (Морфологія / Morphologia / Morfologìâ, 2011)
The article investigates the expression of immunohistochemical markers in squamous oropharyngeal cancers to predict the clinical course. The analysis of marker expression of VEGF and CD34, matrix metalloproteinases 1 and 9, oncoprotein p21, p16, cyclin D1, cell adhesion markers E-cadherin and b-catenin and proliferative activity of Ki-67 depending on the clinical and morphological characteristics of the tumor (primary localization, degree of differentiation, presence of metastases in the lymph nodes in the neck) and responses to chemotherapy. Defined "unfavorable" immunophenotype oropharyngeal cancers with a high risk of metastasis and the likely insensitivity to chemotherapy, which allows a more differentiated approach to the tactics of treatment of patients with squamous cell carcinoma of oropharynx.